Physical culture and sports events as a form of social adaptation of students with health disabilities - Podberezko N.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify students’ attitudes towards physical education and mass events as a form of social adaptation of students with health limitations. Methods and structure of the study. The scientific experiment was conducted at the Department of Physical Education of Altai State University in the 2022-2023 academic year as part of a physical education and sports event dedicated to the 50th anniversary of Altai State University “Adaptive Physical Culture Celebration”, organized for students with health problems and disabilities. The program included a set of physical exercises that students of a special medical group with disabilities and/or health limitations could perform to the best of their abilities and who had necessarily undergone physical training for this event in the discipline “Physical Culture and Sports” (elective). At this event, students were asked to complete a survey. Results and conclusions. Students assigned to a special medical group or health group 3 for health reasons feel the need to participate in various types of physical education and sports activities. This organization of involvement in physical activity makes it possible to increase student motivation, improve communication, and expand the range of knowledge in the field of physical education, sports and a healthy lifestyle.